Meningkatkan Kemampuan Menulis Karangan Narasi Melalui Media Visual Siswa Kelas IXE SMP Negeri 25 Kota Jambi Tahun Ajaran 2017/2018 - Reddiana Pakpahan (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Teaching the writing skills of Bahasa Indonesia to SMP students directed to achieve competencies that can be involved in the ability of students reveal various meanings with the correct steps in the written text of a topic relate to the real experience of daily life – with the emphasis of writing language variations. This research is experimental research; By using a class that is an international class IXE junior high School 25 Jambi city. Based on the ability of the students to write narrative essays by using the visual media acquired spread the value of 77 to 88. The lowest value is 77 and the highest value is 88. So based on the value in the table above can be known the average value of students in writing narrative essays using visual media i.e. the number of scores obtained divided by the number of students (sample) is 2286:28 = 81.64. Thus the result of writing essay based on the word media found in good category with an average value of 81.64. From the two results of the class data of the experiment and the control class, it can be concluded that the ability to write narrative essays using visual media is better than the writing ability of narrative essays by not using media Visual grade IX students E SMP Negeri 25 Jambi City.